2019
DOI: 10.1111/tpj.14458
|View full text |Cite
|
Sign up to set email alerts
|

Determination of protein‐only RNase P interactome in Arabidopsis mitochondria and chloroplasts identifies a complex between PRORP1 and another NYN domain nuclease

Abstract: Summary The essential type of endonuclease that removes 5′ leader sequences from transfer RNA precursors is called RNase P. While ribonucleoprotein RNase P enzymes containing a ribozyme are found in all domains of life, another type of RNase P called ‘PRORP’, for ‘PROtein‐only RNase P’, is composed of protein that occurs only in a wide variety of eukaryotes, in organelles and in the nucleus. Here, to find how PRORP functions integrate with other cell processes, we explored the protein interaction network of PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…This was, however, not true for most mRNAs and the endoribonuclease activities have not been tested in vitro (Stoll and Binder 2016). Coimmunoprecipitation and yeast two-hybrid assays recently showed that PRORP1 physically interacts with MNU2, and the latter also plays a role in tRNA accumulation (Bouchoucha et al, 2019). Because several sequence specific PPR proteins are known or predicted to bind upstream of mitochondrial mRNA 59 mature ends (Ruwe et al, 2016), the current model is that they direct unspecific endoribonucleases to the correct site of processing (Binder et al, 2016).…”
Section: Mitochondrial Endoribonucleasesmentioning
confidence: 99%
“…This was, however, not true for most mRNAs and the endoribonuclease activities have not been tested in vitro (Stoll and Binder 2016). Coimmunoprecipitation and yeast two-hybrid assays recently showed that PRORP1 physically interacts with MNU2, and the latter also plays a role in tRNA accumulation (Bouchoucha et al, 2019). Because several sequence specific PPR proteins are known or predicted to bind upstream of mitochondrial mRNA 59 mature ends (Ruwe et al, 2016), the current model is that they direct unspecific endoribonucleases to the correct site of processing (Binder et al, 2016).…”
Section: Mitochondrial Endoribonucleasesmentioning
confidence: 99%
“…This is our favoured hypothesis, as it fits with the observations that natural Rf proteins with the RfCTD domain are associated with RNA cleavage, whereas those that lack this domain are not. Knowledge about the interaction between RFLs and other partners is limited, but RFL2 is presumed to associate with the endonuclease PRORP1 (Fujii et al ., 2016; Stoll & Binder, 2016), and more recently PRORP1 was reported to directly interact with MNU2 via a specific domain of MNU2 and a proline‐rich motif of PRORP1 (Bouchoucha et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This is our favoured hypothesis, as it fits with the observations that natural Rf proteins with the RfCTD domain are associated with RNA cleavage, whereas those that lack this domain are not. Knowledge about the interaction between RFLs and other partners is limited, but RFL2 is presumed to associate with the endonuclease PRORP1 (Stoll and Binder 2016;Fujii et al 2016), and more recently PRORP1 was reported to directly interact with MNU2 via a specific domain of MNU2 and a proline-rich motif of PRORP1 (Bouchoucha et al 2019).…”
Section: The Rfctd Is Essential For the Proper Function Of Rfl Proteinsmentioning
confidence: 99%